An expert meeting on selected innovations in post-literacy and basic level education in Latin America and the Caribbean: A selective bibliography in literacy, post-literacy and basic level education in the Latin American and Caribbean region - Papen, Uta (UNESCO Institute for Education, 1991)
This bibliography is based on the holdings of the Documentation Centre of the UNESCO Institute for Education. The purpose of this working document is to collect relevant English and Spanish titles on Literacy, Post-Literacy and Basic Level Education in Latin America and the Caribbean. Some of them may be of interest for the work of the expert pool on Latin American and Caribbean experiences in Adult and Continuing Education. Only titles published in 1986 and onwards have been chosen. A summary and short comments are given for most of the English documents.
PRG 4.25/5.15
Keywords: Post-literacy; Basic level education